The new economic geography versus urban economics: an evaluation using local wage rates in Great Britain - Bernard Fingleton (European Regional Science Association (ERSA), 2004)
This paper tests two competing models, one deriving from new economic geography theory (NEG) emphasising varying market potential, the other with a basis in urban economics theory (UE) in which the main emphasis is on producer service linkages. Using wage rate variations across small regions of Great Britain, the paper finds that, taking commuting into account, it is UE theory rather than NEG theory that has explanatory power. However since the two hypotheses are non-nested, the evaluation of the competing hypotheses is difficult and therefore the conclusions are provisional. Nevertheless this paper provides evidence that we should be cautious about the ability of NEG to work at all levels of spatial resolution, and re-emphasises the need to focus on supply-side variations in producer services inputs and labour efficiency variations, including the role of commuting, in local economic analysis.
Keywords: 330